Systematic Literature Review: Phytochemistry and Antimalarial Activity of Carrica Papaya Linn - Merna, Diana; Arief, Maipha Deapati; Keruru, Maria N.; Noywuli, Nicolaus; Kase, Inggrid; Simo, Daniel (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Papaya leaves (Carica papaya L.) have been trusted and proven to antimalarial activity. Currently review information on morphology, phytochemical and pharmacology aspects of the papaya plant (Carica papaya L). Based on a literature study on papaya plants (Carica papaya L.) summarized from ScienceDirect, Google Scholar, Springer with search keys morphology, phytochemical, antimalarial, Carica papaya L, plasmodium falciparum, papaya leaf extract has antimalarial activity against plasmodium falciparum. Qualitative phytochemical analysis of papaya leaf extract (Carica papaya L) showed the presence of alkaloids, flavonoids, saponins, tannins, and glycosides. Flavonoids showed antimalarial activity against P. falcifarum which inhibited the entry of L-glutamine and myoinositol into infected erythrocytes during the intraerthrocytic phase of the Plasmodium life cycle.